Pengaruh Pemberian Insentif dan Stres Kerja Terhadap Kinerja Karyawan di Daerah Kelurahan Larangan Selatan - Tri Indra Pamungkas; Fikri Nopal Idriszal; Fauzi Yazid Chairul (Yayasan Literasi Sains Indonesia, 2022)
The purpose of this study is to describe what it is to provide incentives and work stress and employee performance in the Larangan Selatan District. In addition, to test and analyze the significant influence between incentives and work stress on employee performance simultaneously. This study used a quantitative method, namely distributing questionnaires in which 105 respondents were obtained as a sample and this study used data analysis techniques, the analysis used was statistical analysis with classical assumption testing, t-test hypothesis, f-test hypothesis, assisted determination coefficient test with SPSS software version 21 to find out whether each variable influences each other or not at all. The results of this study are that the provision of incentives has a positive and significant effect on employee performance, work stress has a positive and significant effect on employee performance, the provision of incentives and work stress simultaneously has an effect on employee performance in the South Larangan Sub-District Area. So it can be concluded that the provision of incentives and work stress can affect employee performance. The purpose of this study was to describe what incentives and work stress are and employee performance in the Larangan Selatan Subdistrict Area. In addition, to test and analyze the significant influence between incentives and work stress on employee performance simultaneously. This study used a quantitative method, namely distributing questionnaires in which 105 respondents were obtained as a sample and this study used data analysis techniques, the analysis used was statistical analysis with classical assumption testing, t-test hypothesis, f-test hypothesis, assisted determination coefficient test with SPSS software version 21 to find out whether each variable influences each other or not at all. The results of this study are that the provision of incentives has a positive and significant effect on employee performance, work stress has a positive and significant effect on employee performance, the provision of incentives and work stress simultaneously has an effect on employee performance in the South Larangan Sub-District Area. So it can be concluded that the provision of incentives and work stress can affect employee performance.